EDUKASI PENGOLAHAN SAMPAH BOTOL PLASTIK SEBAGAI ALTERNATIF MEDIA TANAM DALAM PERBAIKAN GIZI DAN KESEHATAN MASYARAKAT - Biswas, Nurani Putri; Yani, Septia Nanda; Marizki, Tiya Yunda; Yusuf, Maulana; Rahmadhani, Esti; Shafira, Tiara Rajjana; Wulandari, Ni Putu; Pratiwi, Muliani Galuh; Rizki, Lalu Setiawan; Wafa, Husnul (Universitas Mataram, 2025)
The problem of household plastic waste and the low utilization of home yards as a source of healthy food is still prevalent in Mendana Raya Village, Keruak District, East Lombok Regency. This condition causes environmental pollution as well as community dependence on vegetable supplies from the market. One alternative solution is utilizing plastic bottles as simple hydroponic growing media, which can simultaneously provide nutritious vegetables for households. This activity aimed to reduce plastic waste generation and improve community skills in transforming plastic bottles into productive planting media. The method consisted of four stages: observation and problem identification, coordination and preparation, implementation of education and training through three meetings, and evaluation and monitoring. The results indicated positive changes within the community. A total of 150 plastic bottles were successfully converted into hydroponic media for lettuce, kale, and pakcoy. Participants showed high enthusiasm and were able to apply hydroponic planting skills independently at home. The positive response was also supported by village officials to ensure program sustainability. Therefore, the objectives of this community service program to provide solutions to environmental problems and to support the availability of nutritious food at the household level have been achieved.